2017
DOI: 10.1016/j.ajo.2017.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Experience of Anti-VEGF Treatment and Clinical Levels of Depression and Anxiety in Patients With Wet Age-Related Macular Degeneration

Abstract: Purpose: To investigate detailed patient experiences specific to receiving vascular endothelial growth factor inhibitors (anti-VEGF) for wet Age-Related Macular Degeneration (wAMD), and to acquire a snapshot of the frequency of clinically significant levels of depression, anxiety and post-traumatic stress among patients and levels of burden in patients' carers. Design: Observational cross-sectional mixed-methods study Methods: 300 patients with wAMD receiving anti-VEGF treatment and 100 patient carers were rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
90
4
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(104 citation statements)
references
References 52 publications
6
90
4
1
Order By: Relevance
“…Thus, DITAMD should be tested in additional sites, preferably in a multicentre, international setting. However, the strength of the current study is its coherence with previous studies that report similar dimensions of importance in nAMD treatment (Kandula et al 2010(Kandula et al , 2010Boyle et al 2015;Senra et al 2016Senra et al , 2017. Kandula et al reported that the patients felt hopeful about the prospect of receiving intravitreal injections which is similar to one of our most frequently reported dimensions: receive treatment to keep vision.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Thus, DITAMD should be tested in additional sites, preferably in a multicentre, international setting. However, the strength of the current study is its coherence with previous studies that report similar dimensions of importance in nAMD treatment (Kandula et al 2010(Kandula et al , 2010Boyle et al 2015;Senra et al 2016Senra et al , 2017. Kandula et al reported that the patients felt hopeful about the prospect of receiving intravitreal injections which is similar to one of our most frequently reported dimensions: receive treatment to keep vision.…”
Section: Discussionsupporting
confidence: 78%
“…Other dimensions included in DITAMD questionnaire such as waiting time, follow up structure, transport/travel, are similar to what has been described as 'treatment burden' in other studies (Droege et al 2014;Boyle et al 2015;Senra et al 2016). Boyle et al 2015;Senra et al 2016Senra et al , 2017. Many of these areas reported in previous studies, including injection technique, the need for information about the disease and progression, and the concern about treatment being effective to keep vision can be recognized in dimensions of the current study (Kandula et al 2010;Tailor et al 2011;Droege et al 2014;Table 4.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Each subscale includes seven items, generating scores between 0 and 21, for anxiety (Cronbach's alpha of 0.89) and depression (Cronbach's alpha of 0.91). A score of 8 and above is widely used to indicate the presence of clinical levels of anxiety or depression that may warrant further psychological investigation …”
Section: Methodsmentioning
confidence: 99%